Pengaruh Online Customer Review Dan Price Terhadap Purchase Decision Melalui Purchase Intention Sebagai Variabel Mediasi (Studi Pada Konsumen The Originote Pada Official Store Di Shopee) - Diva, Divafaradhilah; Ninik Churniawati (Jurnal Transparan Institut Teknologi dan Bisnis Yadika, 2024)
The emergence of competition between marketplaces in the current digital era has caused each marketplace to implement superior marketing strategies to influence purchasing decisions. This makes the consumer review feature a major role in increasing insight regarding preferences regarding the desired product. With the goal of better understanding how purchase intention mediates the relationship between online customer reviews and pricing and final purchase choices, this research set out to do just that. The sampling technique use nonprobability sampling with the purposive sampling method. Eighty individuals were used as samples. This research use quantitative methods. Consumers' intent to buy mediates the effect of online customer reviews on their purchase decisions on Shopee marketplace users, and price and purchase intention both have an impact on consumers' final purchasing decisions. The conclusion is that a product's price and number of positive reviews have a direct correlation to the likelihood that a customer would make a purchase.